Komparasi Pengaruh Square Stepping Exercise dan Tandem Walking Exercise dalam Meningkatkan Keseimbangan Dinamis Lansia - Tri Utami; Fiqi Widyawati; Azizah Rahmawati; Young Ari Kusworo (Lembaga Pengembangan Kinerja Dosen, 2026)
Reduced dynamic balance among older adults is often linked to a greater risk of falling and a decline in functional independence. This study aimed to analyze and compare the effects of Square Stepping Exercise (SSE) and Tandem Walking Exercise (TWE) on dynamic balance in the elderly. A quantitative experimental method with a two-group pretest-posttest design was carried out at the Elderly Posyandu in Ngadiluwih Village, Matesih District, Karanganyar Regency. The study involved 30 older adults who met the inclusion criteria and were divided into two intervention groups, with 15 participants assigned to the SSE group and 15 participants to the TWE group. Each group performed the exercise intervention four times per week for four weeks. Dynamic balance was evaluated using the Timed Up and Go Test (TUGT). The mean TUGT score in the SSE group decreased from 15.84 ± 2.43 seconds to 11.83 ± 2.26 seconds, while the TWE group decreased from 16.36 ± 2.53 seconds to 14.12 ± 2.21 seconds. Both interventions were shown to improve dynamic balance; however, SSE produced a greater improvement than TWE. These findings suggest that SSE can be considered a practical physiotherapy exercise alternative for enhancing balance ability and reducing the risk of falls in older adults.